Unconventional Hund metal in a weak itinerant ferromagnet - Xiang Chen (Nature Portfolio, 2020)
The rich magnetic phase behaviour of MnSi reflects the complexity of the physics underlying itinerant ferromagnetism. Here the authors present evidence that MnSi is strongly influenced by Hund’s coupling effects, suggesting a broader class of materials may fall into the class of Hund metals.